A geochemical study of the Middle Group chromitites, Helena mine, Bushveld complex, South Africa - Kottke-Levin, Janine (University of the Free State, 2011)
The study in hand reports on compositional variations in mineral and whole-rock geochemistry of the chromitite and silicate layers occurring in the Middle Group of the eastern Bushveld Complex. Special attention is paid to the platinum-group element (PGE) content and mineralization as well as the nature of platinum-group minerals (PGM) within the MG sequence. A general progressive evolution of the MG chromitite layers can be deduced from chromite composition showing decreasing Mg# and enrichment of Fe and Al relative to Cr as well as from the decreasing whole-rock Mg#. At the LCZ/UCZ transition no marked change in mineral and whole-rock geochemistry can be observed, indicating that the MG sequence derives from a continuously progressive evolving melt. The presence of one parental magma for the formation of the MG is further substantiated by the chondrite-normalized PGE patterns of the MG chromitite layers, which resemble each other. They further resemble that of the UG2, which suggests that they derive from the same magma and a similar style of mineralisation applied. One marked reset to compositions even more primitive than the MG1 chromitite layer is present at the level of the MG4A chromitite layer, which is illustrated by a low Mg#chr, low whole-rock Mg#, low mineral and whole-rock Cr3+/(Cr3++Fe3+) ratios and increasing mineral and whole-rock Cr3+/(Cr3++Al3+) ratios and TiO2 contents. It strongly suggests the addition of hot and primitive magma at this level of the MG stratigraphy. Whole-rock geochemistry of the silicate layers is strongly governed by mutual influence of co-precipitating minerals competing for major elements like Mg, Fe, Al or Cr, and hence a statement to general trend with respect to evolution from bottom to top of the stratigraphic column of the MG sequence can’t be made. Nevertheless, a strong decrease in whole-rock Mg# and low whole-rock Al2O3 concentrations at the level of the MG4A pyroxenite is illustrated, which can be ascribed to the same event of addition of primitive magma concluded for the MG4A chromitite layer. The existence of Na-rich silicate inclusions occurring in chromite of all the MG chromitite layers most likely proves chromitite formation by mixing of primitive melt with a siliceous melt. Hence, the general process for the formation of the chromitite layers and their corresponding silicate layers in the MG seems to be mixing of a primitive (mafic-ultramafic) parental melt with siliceous roof-rock melt deriving from the granophyric Rooiberg felsites. Although Cu deriving from the base metal sulphides (BMS) seems to migrate away from the chromitite layers, local Cu enrichment in the chromitite layers to concentrations up to >6000 ppm can be observed. This excess Cu most likely derives from an external source e.g. country rocks, which could have ‘generated’ metal-loaded hydrothermal fluids. Excess S occurring in the silicate layers may result from limited, probably hydrothermal, dissolution of BMS from the respective chromitite layer below. Chromitite samples have been investigated with the mineral liberation analyzer (MLA) for their PGM. The study focused on the mineral association of the PGM, i.e. whether they occur liberated, locked or attached to gangue or the BMS, since the mineral association is important to conclude on PGE mineralization and PGM formation. The majority of the PGM occurring in the chromitite layers of the MG sequence are Pt- Rh -sulfides (26.2%), followed by laurite (25%), Pt-Pd -sulfides (24.3%) and Pt -sulfides (13.8%). The remaining 10.7% comprise PGE –sulphoarsenides and PGE- arsenides, Pt - and Pd –alloys and Pt - and Pd –tellurides. Except laurite, which is commonly locked in chromite (66%), the PGM are dominantly associated with silicate minerals, and to a lesser extend with the BMS only. According to this discrepancy in the PGM association, PGE mineralization of the MG chromitite layers most likely can’t be modelled in terms of the R-factor and therefore PGE concentration by the cluster model is favoured by the author. Alteration of the primary silicate minerals in the MG chromitite layers to amphibole, chlorite, talc, mica and quartz can be observed locally. Since the primary BMS assemblage (chalcopyrite, pyrite and pentlandite) shows losses of Fe, Cu and S, and millerite, a Ni-rich sulphide of secondary origin, occurs, the influence of hydrothermal fluids on the chromitite layers was concluded. Besides affecting the BMS, the fluid most likely also redistributed the PGE occurring in solid solution in the BMS, i.e. Pt and Pd, as especially the negative slope from Pt to Pd in the chondrite normalized PGE patterns of the MG chromitite layers suggests. Enrichment of the high-temperature PGE (HT-PGE) over the low-temperature PGE (LT-PGE) is depicted in the chondrite normalized PGE patterns of the MG chromitite and silicate layers. The fact that the HT-PGE are enriched relative to the LT-PGE in the lowermost MG chromitite layers as well as in the MG4A suggests that temperature could play a role in PGE fractionation. Temperature control on PGE fractionation has also been concluded from changing Pt/Ir ratio in dependence of the whole-rock Al2O3 content from bottom to top of the MG sequence, with increasing Al2O3 concentrations considered to point to decreasing temperature. Hence, Al-depletion, i.e. decreasing Al2O3 content, of chromite relative to Cr may result in enrichment of the HT-PGE relative to the LT-PGE. The LT-PGE are preferentially concentrated by increasing amounts of plagioclase within the chromitite layers.
Keywords: Thesis (Ph.D. (Geology))--University of the Free State, 2011; Chromite -- South Africa; Geology -- South Africa; Mineralogy -- South Africa